Insights on Earnings Management: Findings from Indonesian Companies Study - Sambora, Giovanna; Siahaan, Magda (Jurnal Akuntansi, 2025)
Purpose – The purpose of this study was to empirically prove several factors that affect earnings management. In this study, there are several independent variables: managerial ownership, leverage, profitability, rationalization, ineffective monitoring, and audit committee. Design/methodology/approach – Manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2020 are used in this study. The purposive sampling technique was implemented, and 52 companies that satisfied the criteria were included, resulting in 156 data points. Multiple regression data analysis approaches were used throughout the study. Findings – This study demonstrates how leverage, profitability, and rationalization variables affect earnings management. Meanwhile, managerial ownership, poor monitoring, and audit committee factors had little effect on earnings management. Research limitations/implications –This study implies that companies need to pay attention to factors that influence earnings management, such as profitability and leverage, as well as increase transparency and accountability to maintain the integrity of financial reports and build market trust. Keywords: Audit Committee, Earnings Management, Ineffective Monitoring, Managerial Ownership, Rationalization